FRAUD PREVENTION THROUGH STRUCTURE OF INTERNAL CONTROL AND SPIRITUAL ACCOUNTING - Andi Arifwangsa Adiningrat (Politeknik Negeri Bengkalis, 2022)
This research is about fraud prevention through control structure and spiritual accounting. Fraud occurs because of three main things, namely: the pressure to commit fraud, the opportunities that can be exploited and the justification for these actions, The tendency for accounting fraud has attracted a lot of media attention and has become a prominent and important issue in the eyes of world business. An auditor must make every effort to prevent fraud. Fraud prevention can be analogous to disease, that is, prevention is better than cure. This study aims to measure the effect of implementing internal control structures and spiritual accounting on preventing fraud. The specific target to be achieved is to minimize fraud committed by company management. In this research, the analytical method used is multiple linear regression analysis. Multiple linear regression analysis method consists of two analytical tools, namely Descriptive Statistical Analysis and Infensial Statistical Analysis. The results show that the internal control structure has a negative effect on the auditor's ability to prevent fraud, while spiritual accounting has a positive effect on the auditor's ability to prevent fraud.